Maximizing Carbon Credit Generation: A Comprehensive Analysis of Hybrid Photovoltaic Thermal Arrays - Singh, Dipti (Journal of Advanced Research in Petroleum Technology & Management; Vol 9 No 1&2 (2023): Journal of Advanced Research in Petroleum Technology and Management, 2023)
The hybrid photovoltaic thermal (PVT) array's ability to earn carbon credits has been examined in this paper. The study's methodology was based on the PVT array's overall thermal and exergy output. A system made up of 36 hybrid PVT modules coupled in series and parallel is called the hybrid PVT array. By taking into account Bangalore's four sorts of weather conditions (a, b, c, and d types), the annual energy and exergy gain has been assessed. This article provides the total carbon credit obtained by in accordance with Bangalore climate standards of the Kyoto Protocol.